The Impact of Electronic Accounting Information Systems on the Security of Financial Information - Ahmed Kadhim Sendw (Indonesian Journal Publisher, 2025)
This study aimed to prove the security of financial information through the confidentiality and non-disclosure of information by individuals. To achieve this objective, the research addressed the knowledge bases and theoretical foundations of electronic accounting information systems (EAIS) and their relationship to accounting books and documents. It also discussed financial information security (FIS), its importance, elements, and components, and clarified the competence and effectiveness of accounting information systems implemented in government departments. Furthermore, it determined the importance of financial information confidentiality in government units, given that FIS constitutes a fundamental pillar of the administrative system within economic units. This is due to its role in protecting user information, whether for government units or stakeholders involved in decision-making, through reliance on accounting information systems. The research reached several conclusions, most notably the global interest in EAIS due to their significant advantages in the field of FIS. Additionally, the readiness of the system used in a company helps meet the requirements for protecting FIS